The impact of public health education on people's demand for commercial health insurance: Empirical evidence from China - Gao, Lifei; Nie, Ying; Wang, Guojun; Li, Fei (Frontiers in Public Health, 2022)
Public health education is gaining significance globally, and is important for managing increasing health risks. This study empirically analyzed the effect of public health education on people's demand for commercial health insurance based on panel data of 31 provinces (including municipalities and autonomous regions) in China from 2009–2019, using the fixed effects and the mediating effect models, and instrumental variables regression. The findings show that public health education significantly increases people's demand for commercial health insurance, and this effect remains significant even after overcoming endogenous problems and robustness tests. We further analyzed and found that increased demand for commercial health insurance is caused by improved health literacy, health risk perceptions and changing health risk attitudes. Through heterogeneity analysis, we found that there were significant differences in the effects of public health education in regions with different demographic and socioeconomic characteristics. We found that the effect of health education on promoting people's demand for commercial health insurance is more obvious in regions with high levels of urbanization, proportion of men, education, economic development, medical resources, and social medical insurance coverage. Governments are supposed to take further measures to enhance the effectiveness of public health education, develop high-quality commercial health insurance, and continuously improve health risk coverage.